EFFECT OF TWO ANTIOXIDANTS (TEMPO AND TEMPOL) ON RAM SEMEN CRYOPRESERVATION USING THE TRIS EXTENDER - Ruiz G., Luis (2007)
Thirty-two semen samples from four rams were frozed using two antioxidants, Tempo (2,2,6,6 tetramethyl-1-piperidinyloxyl) and Tempol (4-hidroxi 2,2,6,6 tetramethyl-1- piperidinyloxyl), each one in concentrations of 0.5, 1.0, and 2.5 mM, to evaluate the effects on post-thawing motility, viability, acrosomal integrity, and earlier sperm capacitation. Eight replications for each antioxidant concentration and control group, were done using four semen samples per replication. Semen samples were diluted on a Tris extender. Results showed that Tempo 0.5 mM improved frozen semen quality in comparison with control group (p<0.05), by increasing progresive motility (79 vs. 67%), viability and acrosomal integrity (70 vs. 58%), and decreasing earlier sperm capacitation (9 vs. 15%). On the other hand, Tempol decreased frozen semen quality. In conclusion, the use of Tempo 0.5 mM on a Tris extender, at the end of the cooling process, could be an alternative for improving the quality of frozed ram semen.